The Effect of Ballon Blowing Exercise on Respiratory Rate in Patients Chronic Obtructive Pulmonary Disease at Sumberglagah Regional Hospital - Nikmatus Shivany, Lisfia; Virda Yuniarti, Enny; Merbawani, Raras Merbawani (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
Chronic Obstructive Pulmonary Disease (COPD) is a chronic lung disease characterized by persistent and progressive airflow obstruction. This can trigger an increase in respiratory rate due to shortness of breath. The purpose of this study was to determine the effect of Balloon Blowing Exercise on respiratory rate in COPD patients. This study used a pre-experimental design with a one-group pre-test and post-test approach. The study population was all COPD patients in the inpatient unit of Sumberglagah Regional Hospital, Pacet District, Mojokerto Regency, with a sample of 30 respondents taken through a purposive sampling technique. Data collection was carried out by measuring respiratory rate before and after the intervention. Data analysis used the Wilcoxon Signed Rank-Test. The results showed a p-value of 0.000 or <ÿ (0.05), which means there is a significant effect of Balloon Blowing Exercise on respiratory rate in COPD patients. Research on Balloon Blowing Exercise has proven effective in reducing the Respiratory Rate, because this exercise can extend the expiratory phase which triggers the release of more CO2 from the lungs and involves the respiratory muscles, so that by improving ventilation, preventing water trapping and respiratory muscle training can reduce the workload of the respiratory system, which has an impact on reducing the respiratory frequency.